E-049 Intraprocedural Diagnosis of Flow-Diverting Stent Malapposition during Endovascular Aneurysm Treatment with DynaCT Imaging. (26th July 2014) - Ding, D; Starke, R; Durst, C; Gaughen, J; Evans, A; Jensen, M; Liu, K
Abstract : Introduction: The treatment of large, complex intracranial aneurysms is being increasingly performed using flow-diverting stents (FDS) such as the Pipeline Embolization Device (PED). Malapposition of a FDS to the parent artery wall decreases the likelihood of aneurysm obliteration and increases the risk of both immediate and delayed complications. DynaCT is a novel imaging modality which uses a flat plane detector to generate computed tomography images using the same C-arm employed for digital subtraction angiography. Methods: We present a case of a 40 year-old female with a large, unruptured, cavernous internal carotid artery (ICA) aneurysm who was treated with endovascular obliteration using a PED. Results: A 6 French Chaperon guide catheter was navigated into the left ICA through which subsequent control angiograms could be performed. Cerebral angiography showed a lobular, cavernous ICA aneurysm measuring 11 mm in maximal diameter with a wide 7.5 mm neck. An Excelsior XT-27 microcatheter advanced over an Asahi Chikai microguidewire into the M1 segment of the middle cerebral artery (MCA). A 4.75 × 20 mm PED was advanced through the XT-27 microcatheter and deployed across the aneurysm neck. After removing the XT-27 microcatheter, a control angiogram through the Chaperon guide catheter showed appropriate position of the PED in relation to the aneurysm. Intraprocedural DynaCT was performed after PED deployment to critically assess apposition of the PED to the wall of the parent artery. The injection parameters for the DynaCT were as follows: 20 sec rotation, 3 mL contrast per sec, 0.2 rate rise, injection at 300 psi, and X-ray delay of 2 sec following initiation of injection. The radiation parameters were as follows: 70 kV, pulse width 12.5 msec, dose 1200 μGy per hour, total angle 200o, angulation step 0.4o per frame. The DynaCT revealed a slight overhang of the distal portion of the PED which could not be identified on angiography (Figure ). Based on these findings, an angioplasty of the distal PED was performed using a 4 × 10 mm TransForm balloon. Following removal of the balloon, a final control angiogram was performed which showed no evidence of intraprocedural complications. The patient remained neurologically stable following PED treatment and was discharged home the next day. Conclusions: While gross stent malapposition is readily evident after stent deployment, minor instances of malapposition may be undetectable by standard angiography. Therefore the use of DynaCT may improve intraprocedural stent visualization and potentially avert long-term endovascular aneurysm treatment complications associated with inadequate stent apposition. Disclosures: D. Ding: None. R. Starke: None. C. Durst: None. J. Gaughen: None. A. Evans: None. M. Jensen: None. K. Liu: None.